MINERÍA Y CONTAMINACIÓN AMBIENTAL EN PIURA - Piscoya Arbañil, Julio Alberto (2019)
Objective: To determine the existence of environmental contamination by mining in Piura. Material and Methods: A descriptive, transversal, observational study, using papers and publications on the subject nationally and abroad. Triangulation was conducted of all the theoretical and empirical. Results: We found evidence of contamination in air, soil and water with products such as cyanide and mercury. Informal mining (which produces 24 tons. of gold per year). The problem becomes uncontrollable by widespread ignorance of the localities where they practice and lack of environmental impact studies, which generate little development of these communities. There are areas of illegal activity in Amazonas, Loreto, Ucayali, Loreto, Puno, Huánuco, Ica, Arequipa, Ayacucho, Cusco, Cajamarca, La Libertad, Piura, Lima, Pasco, Tacna and Moquegua. Conclusion: There contamination soil, air, water, land subsidence, noise and vibration, waste and wastewater, acid rock drainage (ARD) that generates acid waters with metal sulfates, risk of failure of tailings deposits, sediment erosion of tailings, precipitated Fe (OH) 3. Presence of environmental liabilities. In the mining industry in Peru is developing environmental consciousness of the great mining, but not in the small and artisanal mining, environmental impacts are known with a partial diagnosis of environmental liabilities. It was evident that among the metals that exceed allowable limits according to international standards in the Piura river, are: Ba, Cr, Al, Cd, Ca, Fe, Hg, Ir, Mg, Mo, Ni, Pb, Si, Sr., Te, Ti, V, W, Zn, Zr.